Vibration spectroscopy, X-ray diffraction, scanning electron microscopy and computational simulation data related to the growth of Li-carbonate crystals in different solutions - Helen E King; Nelson Y Dzade; Oliver Plümper (PANGAEA, 2019)
Data collected as part of a research study examining the growth of lithium carbonate (mineral name: zabuyelite, chemical formula: Li2CO3) from aqueous solution in the presence of inorganic additives. Ion-pair interactions within the solutions were examined using Raman spectroscopy, whereas the interactions between precipitated crystals and aqueous solution was tested using attenuated total reflectance infrared spectroscopy. In addition, computational simulations were used to study ion pairing in solution (PHREEQC) and adsorption to crystal surfaces (VASP). Precipitates from the experiments were characterised using Raman spectroscopy, diffuse reflectance Fourier transform infrared spectroscopy (DRIFTS) and X-ray diffraction (XRD). Images of the precipitates were obtained using scanning electron microscopy (SEM). For details of the set up for each instrument and specific parameters for the computational simulations, please see the linked publication.
Supplement to: King, Helen E; Salisbury, A; Huijsmans, J; Dzade, Nelson Y; Plümper, Oliver (2019): Influence of Inorganic Solution Components on Lithium Carbonate Crystal Growth. Crystal Growth & Design, 19(12), 6994-7006, https://doi.org/10.1021/acs.cgd.9b00782